2011
DOI: 10.1103/physrevb.84.134429
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport of the quasi-one-dimensional alternating spin chain material (CH3)2NH2CuCl

Abstract: We report a study of the low-temperature heat transport in the quasi-one-dimensional S = 1/2 alternating antiferromagnetic-ferromagnetic chain compound (CH 3 ) 2 NH 2 CuCl 3 . Both the temperature and magnetic-field dependencies of thermal conductivity are very complicated, pointing to the important role of spin excitations. It is found that magnetic excitations act mainly as the phonon scatterers in a broad temperature region from 0.3 to 30 K. In magnetic fields, the thermal conductivity shows drastic changes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Using x-ray Laue photographs, the large pieces of crystals were cut into thin-plate or long-bar shaped samples with specific orientations. The thermal conductivity was measured at low temperatures down to 0.3 K and in magnetic fields up to 14 T by using a conventional steadystate technique [20,22,24,38]. In these measurements, the magnetic field is either parallel to or perpendicular to the heat current (J H ), which is along the length of the sample ( ∥ J b H ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using x-ray Laue photographs, the large pieces of crystals were cut into thin-plate or long-bar shaped samples with specific orientations. The thermal conductivity was measured at low temperatures down to 0.3 K and in magnetic fields up to 14 T by using a conventional steadystate technique [20,22,24,38]. In these measurements, the magnetic field is either parallel to or perpendicular to the heat current (J H ), which is along the length of the sample ( ∥ J b H ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in zero field the temperature dependence of κ is very complicated. A peculiar feature of the ( ) κ T is a three-peak structure at about 2, 8 and 100 K. The positions of these peaks are rather different from that of phonon peak in insulators, which usually locates at 10-20 K. Considering the small values of κ, these peaks are actually caused by the presence of two valley-like minimums at 3 and 17 K. In general, the possible reasons of these minimums in ( ) κ T curves of the magnetic materials could be either the strong phonon scattering by critical spin fluctuations at some magnetic phase transitions or the phonon resonant scattering by some magnetic impurities or lattice defects [15,22,23,28,34,[48][49][50][51][52][53][54]. It has been known that Cu 3 (CO 3 ) 2 (OH) 2 does not exhibit any magnetic phase transition at 3 and 17 K, as the magnetic susceptibility and specific heat data indicate.…”
Section: E3mentioning
confidence: 99%
See 2 more Smart Citations
“…The Kitaev model [1] has attracted particular attention, both theoretically and experimentally, because it possesses an exactly solvable quantum spin-liquid (QSL) ground state and has possible realizations in a number of candidate materials [2][3][4][5]. Thermal transport measurements have proven to be a powerful tool for elucidating the itinerant nature of QSLs [6,7], as a result of their high sensitivity to the low-energy excitation spectrum, and in fact studies of low-dimensional insulating quantum magnets have revealed very significant contributions to heat conduction from unconventional spin excitations [8][9][10][11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%